Engineered Silybin Nanoparticles Educe Efficient Control in Experimental Diabetes - Roy, Partha; Das, Suvadra; Pal, Rajat; Auddy, Runa Ghosh; Chakraborti, Abhay Sankar; Mukherjee, Arup (Public Library of Science, 2014)
Silybin, is one imminent therapeutic for drug induced hepatotoxicity, human prostrate adenocarcinoma and other degenerative organ diseases. Recent evidences suggest that silybin influences gluconeogenesis pathways favorably and is beneficial in the treatment of type 1 and type 2 diabetes. The compound however is constrained due to solubility (0.4 mg/mL) and bioavailabilty limitations. Appropriate nanoparticle design for silybin in biocompatible polymers was thus proposed as a probable solution for therapeutic inadequacy. New surface engineered biopolymeric nanoparticles with high silybin encapsulation efficiency of 92.11% and zeta potential of +21 mV were designed. Both the pure compound and the nanoparticles were evaluated in vivo for the first time in experimental diabetic conditions. Animal health recovered substantially and the blood glucose levels came down to near normal values after 28 days treatment schedule with the engineered nanoparticles. Restoration from hyperglycemic damage condition was traced to serum insulin regeneration. Serum insulin recovered from the streptozotocin induced pancreatic damage levels of 0.17±0.01 µg/lit to 0.57±0.11 µg/lit after nanoparticle treatment. Significant reduction in glycated hemoglobin level, and restoration of liver glycogen content were some of the other interesting observations. Engineered silybin nanoparticle assisted recovery in diabetic conditions was reasoned due to improved silybin dissolution, passive transport in nanoscale, and restoration of antioxidant status.